Short-Term Tinnitus Suppression With Electric-Field Guided rTMS for Individualizing rTMS Treatment: A Technical Feasibility Report - Schoisswohl, Stefan; Langguth, Berthold; Schecklmann, Martin (Frontiers in Neurology, 2020)
Background: Past research highlighted the benefits of personalized rTMS for the treatment of chronic subjective tinnitus. Objective/ Hypothesis: The objective was to investigate the feasibility of rTMS personalization by identifying individually optimal stimulation parameters in test sessions. Particularly, effectiveness and retest-reliability of different stimulation parameters were examined. Methods: Via electric-field guided rTMS, 5 patients were stimulated with different frequencies on three positions of the left and right superior temporal gyrus on two separate days. After each stimulation the patients had to evaluate tinnitus loudness and discomfort of the used protocol. Results: Individualization of rTMS was possible in all five patients. Significant lower tinnitus loudness was found for 1 Hz stimulation. Positive correlations between two days were observed for hemisphere (left, right), position (mSTG, pSTG) and frequency (1, 10, 20 Hz). High frequency stimulation produced high discomfort. Conclusion: Personalization of rTMS is considered as feasible. Consistency of parameter-specific tinnitus suppression is demonstrated.